Can Earth's and Society's Systems Meet the Needs of 10 Billion People?: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
The Earth's population, currently 7.2 billion, is expected to rise at a rapid rate over the next 40 years. Current projections state that the Earth will need to support 9.6 billion people by the year 2050, a figure that climbs to nearly 11 billion by the year 2100. At the same time, most people envision a future Earth with a greater average standard of living than we currently have - and, as a result, greater consumption of our planetary resources. How do we prepare our planet for a future population of 10 billion? How can this population growth be achieved in a manner that is sustainable from an economic, social, and environmental perspective? Can Earth's and Society's Systems Meet the Needs of 10 Billion People? is the summary of a multi-disciplinary workshop convened by the National Academies in October 2013 to explore how to increase the world's population to 10 billion in a sustainable way while simultaneously increasing the well-being and standard of living for that population. This report examines key issues in the science of sustainability that are related to overall human population size, population growth, aging populations, migration toward cities, differential consumption, and land use change, by different subpopulations, as viewed through the lenses of both social and natural science.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Perspectives on Climate and Environmental Justice on the U.S. Gulf Coast: Proceedings of a Webinar–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Communities along the Gulf Coast routinely experience intense weather events. Acute and repetitive shocks - illustrated by the multiple Gulf regional hurricane landfalls during the 2020 hurricane season - have a disproportionate impact on communities in this region that are already burdened by chronic stressors such as systemic and structural racism, poverty, environmental degradation, and health disparities. Climate change threatens to exacerbate the severity of these impacts as disadvantaged and underserved communities fall further behind in their ability to prepare for, respond to, mitigate, or recover from disasters. On June 24, 2021, the Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine convened a panel of three members of the White House Environmental Justice Advisory Council to discuss steps that are being taken or that need to occur to advance climate and environmental justice for those who call the Gulf of Mexico region home. The panelists discussed opportunities to equitably improve conditions in the Gulf of Mexico region, particularly within Black, Indigenous, and People of Color communities. This event provided important perspective, though much work remains to elevate and examine the climate and environmental justice priorities of diverse communities, particularly Indigenous people, and to identify the mechanisms necessary to implement the recommendations offered by the panel members. This publication summarizes the discussion.
Keywords: Environment and Environmental Studies

Communities, Climate Change, and Health Equity: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As the effects of climate change become more widespread and significant, communities least able to respond are bearing the largest burden. In the United States, communities disadvantaged by a legacy of racial segregation and environmental injustice struggle with disparate health outcomes, are vulnerable to the effects of climate change (e.g., severe flooding in low-lying areas and extreme heat in urban neighborhoods), and lack sufficient resources to recover from and rebuild for resilience against future events. On October 12 and 14, 2021, the 2-day virtual workshop "Communities, Climate Change, and Health Equity - A New Vision" brought together environmental health experts, resilience practitioners, climate scientists, and people with lived experience to discuss the disproportionate impact of climate change on communities experiencing health disparities and environmental injustice. During the workshop, the first in a four-part series, 41 speakers shared their perspectives on the topic and suggested specific actions that decision-makers can take to address the intersecting crises of climate change and health inequity. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

A Review of the Draft 2013 National Climate Assessment - National Research Council (The National Academies Press, 2013)
As mandated by the Global Change Research Act (GCRA), the U.S. Global Change Research Program is currently producing a "National Climate Assessment" (NCA). The NCA is a report to inform the President, the Congress, and the American people about the current state of scientific knowledge regarding climate change effects on U.S. regions and key sectors, now and in the coming decades. This document contains an evaluation of the draft NCA report, presented through consensus responses to the Panel's Task Statement questions, and through a large collection of individual Panel member comments and suggestions for specific chapters, statements, figures, etc. While focusing primarily on practical suggestions for immediately improving the current draft, the Panel also raises some broader considerations about fundamental approaches used in certain parts of the NCA report, and about the scope of USGCRP research that underlies the NCA findings. Some suggestions can be viewed as longer-term advice for future versions of NCA work. This NCA has been a significantly more ambitious effort than previous assessments, in terms of the scope of topics addressed and the breadth of public engagement processes involved. Some of the important new areas include the use of "traceable accounts," the articulation of needs for future research and a vision for an ongoing assessment process, the outreach efforts to help various stakeholders define their climate-related information needs, and the initial (though incomplete) effort to assess the current state of climate change response activities around the nation. Given the current state of the science and the scope of resources available, we believe the NCA did a reasonable job of fulfilling its charge overall. Although more needs to be done to fully meet the nation's needs for information and guidance, such needs cannot be met without an expanded research effort on the part of the USGCRP and future assessments. The Panel suggests that the NCA report would be improved by addressing the numerous specific problems and concerns and the more cross-cutting issues raised in the consensus answers to the Task Statement questions—which include, for instance, the need to: 1. provide a clear overarching framework for the report that helps readers understand climate change as part of a complex system with interacting physical, biological, and human social/economic dimensions, and offers practical guidance on using iterative risk management strategies to make decisions in the face of large uncertainties; 2. clearly acknowledge how climate change affects and is affected by other types of major global environmental changes and other societal developments; 3. offer an explicit discussion about the uncertainties associated with the regional model projections presented in the NCA draft; 4. take full advantage of the e-book format planned for this document through strategic use of hyperlinks among different parts of the report and other innovative approaches that help guide the experience of the NCA's diverse audiences. As the nation continues to engage with the threats, opportunities, and surprises of climate change in its many manifestations, the 2013 NCA should prove to be a valuable resource, as a summary of the state of knowledge about climate change and its implications for the American people.
Keywords: Earth Sciences; Behavioral and Social Sciences; Environment and Environmental Studies

A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field. A Framework for K-12 Science Education outlines a broad set of expectations for students in science and engineering in grades K-12. These expectations will inform the development of new standards for K-12 science education and, subsequently, revisions to curriculum, instruction, assessment, and professional development for educators. This book identifies three dimensions that convey the core ideas and practices around which science and engineering education in these grades should be built. These three dimensions are: crosscutting concepts that unify the study of science through their common application across science and engineering; scientific and engineering practices; and disciplinary core ideas in the physical sciences, life sciences, and earth and space sciences and for engineering, technology, and the applications of science. The overarching goal is for all high school graduates to have sufficient knowledge of science and engineering to engage in public discussions on science-related issues, be careful consumers of scientific and technical information, and enter the careers of their choice. A Framework for K-12 Science Education is the first step in a process that can inform state-level decisions and achieve a research-grounded basis for improving science instruction and learning across the country. The book will guide standards developers, teachers, curriculum designers, assessment developers, state and district science administrators, and educators who teach science in informal environments.
Keywords: Education

Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science—whether using knowledge or creating it—necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy. Science literacy is desirable not only for individuals, but also for the health and well- being of communities and society. More than just basic knowledge of science facts, contemporary definitions of science literacy have expanded to include understandings of scientific processes and practices, familiarity with how science and scientists work, a capacity to weigh and evaluate the products of science, and an ability to engage in civic decisions about the value of science. Although science literacy has traditionally been seen as the responsibility of individuals, individuals are nested within communities that are nested within societies—and, as a result, individual science literacy is limited or enhanced by the circumstances of that nesting. Science Literacy studies the role of science literacy in public support of science. This report synthesizes the available research literature on science literacy, makes recommendations on the need to improve the understanding of science and scientific research in the United States, and considers the relationship between scientific literacy and support for and use of science and research.
Keywords: Education

Climate Change Education in Formal Settings, K-14: A Workshop Summary - National Research Council (The National Academies Press, 2012)
Climate change is occurring, is very likely caused by human activities, and poses significant risks for a broad range of human and natural systems. Each additional ton of greenhouse gases emitted commits us to further change and greater risks. In the judgment of the Committee on America's Climate Choices, the environmental, economic, and humanitarian risks of climate change indicate a pressing need for substantial action to limit the magnitude of climate change and to prepare to adapt to its impacts. A principal message from the recent National Research Council report, America's Climate Choices, this brief summary of how climate change will shape many aspects of life in the foreseeable future emphasizes the vital importance of preparation for these changes. The report points to the importance of formal and informal education in supporting the public's understanding of those challenges climate change will bring, and in preparing current and future generations to act to limit the magnitude of climate change and respond to those challenges. Recognizing both the urgency and the difficulty of climate change education, the National Research Council, with support from the National Science Foundation, formed the Climate Change Education Roundtable. The roundtable brings together federal agency representatives with diverse experts and practitioners in the physical and natural sciences, social sciences, learning sciences, environmental education, education policy, extension education and outreach, resource management, and public policy to engage in discussion and explore educational strategies for addressing climate change. Two workshops were held to survey the landscape of climate change education. The first explored the goals for climate change education for various target audiences. The second workshop, which is the focus of this summary, was held on August 31 and September 1, 2011, and focused on the teaching and learning of climate change and climate science in formal education settings, from kindergarten through the first two years of college (K-14). This workshop, based on an already articulated need to teach climate change education, provided a forum for discussion of the evidence from research and practice. The goal of this workshop was to raise and explore complex questions around climate change education, and to address the current status of climate change education in grade K-14 of the formal education system by facilitating discussion between expert researchers and practitioners in complementary fields, such as education policy, teacher professional development, learning and cognitive science, K-12 and higher education administration, instructional design, curriculum development, and climate science. Climate Change Education in Formal Settings, K-14: A Workshop Summary summarizes the two workshops.
Keywords: Earth Sciences; Education

Addressing Significant Weather Impacts on Airports: Quick Start Guide and Toolkit - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Report 160: Addressing Significant Weather Impacts on Airports provides a web toolkit that raises airport operator awareness about vulnerabilities caused by significant weather events. The toolkit helps airports develop more robust contingency and recovery plans, in addition to their airport emergency plans. This toolkit focuses on events that are “rare but plausible”; that is, events that may have happened in the distant past, or in adjacent geographic areas, but are not common event types at the airport itself, and therefore may not be in the forefront of the airport managers’ minds. The Quick Start Guide provides guidance for using the toolkit.Disclaimers: The opinions and conclusions expressed or implied in this material are those of the researchers who performed the research. They are not necessarily those of the Transportation Research Board, the Academies, or the program sponsors. Materials noted with an asterisk (*) have been edited by TRB; otherwise, materials are as supplied by the contractor.Any digital files or software included is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Adapting to the Impacts of Climate Change - National Research Council (The National Academies Press, 2010)
Across the United States, impacts of climate change are already evident. Heat waves have become more frequent and intense, cold extremes have become less frequent, and patterns of rainfall are likely changing. The proportion of precipitation that falls as rain rather than snow has increased across the western United States and Arctic sea ice has been reduced significantly. Sea level has been rising faster than at any time in recent history, threatening the natural and built environments on the coasts. Even if emissions of greenhouse gases were substantially reduced now, climate change and its resulting impacts would continue for some time to come. To date, decisions related to the management and protection of the nation's people, resources, and infrastructure have been based on records in the recent past, when climate was relatively stable. Adapting to the Impacts of Climate Change, part of the congressionally requested America's Climate Choices suite of studies, calls for a new paradigm-one that considers a range of possible future climate conditions and impacts that may be well outside the realm of past experience. Adaptation requires actions from many decision makers in federal, state, tribal, and local governments; the private sector; non-governmental organizations; and community groups. However, current efforts are hampered by a lack of solid information about the benefits, costs, and effectiveness of various adaptation options; climate information on regional and local scales; and a lack of coordination. Adapting to the Impacts of Climate Change calls for a national adaptation strategy that provides needed technical and scientific resources, incentives to begin adaptation planning, guidance across jurisdictions, shared lessons learned, and support of scientific research to expand knowledge of impacts and adaptation.
Keywords: Earth Sciences; Environment and Environmental Studies

Lessons and Legacies of International Polar Year 2007-2008 - National Research Council (The National Academies Press, 2012)
International Polar Year 2007-2008 (IPY) was an intense, coordinated field campaign of observations, research, and analysis. It was the largest, most comprehensive campaign ever mounted to explore Earth's polar domains. Legacies and Lessons of the International Polar Year 2007-2008 summarizes how IPY engaged the public to communicate the relevance of polar research to the entire planet, strengthened connections with the Indigenous people of the Arctic, and established new observational networks. Legacies and Lessons of the International Polar Year 2007-2008 also addresses the objectives articulated for IPY in the 2004 National Research Council report, A Vision for International Polar Year (NRC, 2004). These objectives include: suggestions for scientific communities and agencies to use the IPY to initiate a sustained effort aimed at assessing large-scale environmental change and variability in the polar regions, the need to explore new scientific frontiers from the molecular to the planetary scale, investment in critical infrastructure and technology to guarantee that IPY 2007-2008 leaves enduring benefits for the nation and for the residents of northern regions, as well as increase public understanding of the importance of polar regions in the global system. Legacies and Lessons of the International Polar Year 2007-2008 explains how activities at both poles led to scientific discoveries that provided a step change in scientific understanding and helped translate scientific knowledge into policy-relevant information. At a time when the polar regions are undergoing a transformation from an icy wilderness to a new zone for human affairs, these insights could not be more timely or more relevant. From outreach activities that engaged the general public to projects that brought researchers from multiple disciplines and several nations together, the legacies of IPY extend far beyond the scientific results achieved, and valuable lessons learned from the process will guide future endeavors of similar magnitude.
Keywords: Earth Sciences

Climate Change: Evidence and Causes: Update 2020 (The National Academies Press, 2020)
Climate change is one of the defining issues of our time. It is now more certain than ever, based on many lines of evidence, that humans are changing Earth's climate. The Royal Society and the US National Academy of Sciences, with their similar missions to promote the use of science to benefit society and to inform critical policy debates, produced the original Climate Change: Evidence and Causes in 2014. It was written and reviewed by a UK-US team of leading climate scientists. This new edition, prepared by the same author team, has been updated with the most recent climate data and scientific analyses, all of which reinforce our understanding of human-caused climate change. Scientific information is a vital component for society to make informed decisions about how to reduce the magnitude of climate change and how to adapt to its impacts. This booklet serves as a key reference document for decision makers, policy makers, educators, and others seeking authoritative answers about the current state of climate-change science.
Keywords: Environment and Environmental Studies

Climate Change Education: Preparing Future and Current Business Leaders: A Workshop Summary - National Research Council (The National Academies Press, 2014)
Climate change poses challenges as well as opportunities for businesses and, broadly speaking for the entire economy. Businesses will be challenged to provide services or products with less harmful influence on the climate; respond to a changing policy, regulatory, and market environment; and provide new services and products to help address the challenges of a changing climate. Many businesses are beginning to see climate change as another context within which they need to consider their core functions of strategy, finance, operations, marketing, and their regulatory environments, a context that poses both risks and opportunities. Climate Change Education: Preparing Current and Future Business Leaders is the summary of a workshop hosted by the National Research Council's Board on Science Education in March 2013 to explore issues associated with teaching climate change-related topics in business schools. The workshop focused on major gaps in understanding of climate and sustainability education in postsecondary professional schools of business. The workshop also connected the topic of climate education for current and future business leaders with a broader discussion on climate change education and how they influence and can benefit each other. This report discusses the role that business schools could play in preparing future corporate leaders for the challenges and opportunities that climate change poses.
Keywords: Environment and Environmental Studies; Education; Earth Sciences

Communicating Science Effectively: A Research Agenda - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Science and technology are embedded in virtually every aspect of modern life. As a result, people face an increasing need to integrate information from science with their personal values and other considerations as they make important life decisions about medical care, the safety of foods, what to do about climate change, and many other issues. Communicating science effectively, however, is a complex task and an acquired skill. Moreover, the approaches to communicating science that will be most effective for specific audiences and circumstances are not obvious. Fortunately, there is an expanding science base from diverse disciplines that can support science communicators in making these determinations. Communicating Science Effectively offers a research agenda for science communicators and researchers seeking to apply this research and fill gaps in knowledge about how to communicate effectively about science, focusing in particular on issues that are contentious in the public sphere. To inform this research agenda, this publication identifies important influences – psychological, economic, political, social, cultural, and media-related – on how science related to such issues is understood, perceived, and used.
Keywords: Policy for Science and Technology

Forest Health and Biotechnology: Possibilities and Considerations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The American chestnut, whitebark pine, and several species of ash in the eastern United States are just a few of the North American tree species that have been functionally lost or are in jeopardy of being lost due to outbreaks of pathogens and insect pests. New pressures in this century are putting even more trees at risk. Expanded human mobility and global trade are providing pathways for the introduction of nonnative pests for which native tree species may lack resistance. At the same time, climate change is extending the geographic range of both native and nonnative pest species. Biotechnology has the potential to help mitigate threats to North American forests from insects and pathogens through the introduction of pest-resistant traits to forest trees. However, challenges remain: the genetic mechanisms that underlie trees' resistance to pests are poorly understood; the complexity of tree genomes makes incorporating genetic changes a slow and difficult task; and there is a lack of information on the effects of releasing new genotypes into the environment. Forest Health and Biotechnology examines the potential use of biotechnology for mitigating threats to forest tree health and identifies the ecological, economic, and social implications of deploying biotechnology in forests. This report also develops a research agenda to address knowledge gaps about the application of the technology.
Keywords: Environment and Environmental Studies; Biology and Life Sciences

Reckoning with the U.S. Role in Global Ocean Plastic Waste - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
An estimated 8 million metric tons (MMT) of plastic waste enters the world's ocean each year - the equivalent of dumping a garbage truck of plastic waste into the ocean every minute. Plastic waste is now found in almost every marine habitat, from the ocean surface to deep sea sediments to the ocean's vast mid-water region, as well as the Great Lakes. This report responds to a request in the bipartisan Save Our Seas 2.0 Act for a scientific synthesis of the role of the United States both in contributing to and responding to global ocean plastic waste. The United States is a major producer of plastics and in 2016, generated more plastic waste by weight and per capita than any other nation. Although the U.S. solid waste management system is advanced, it is not sufficient to deter leakage into the environment. Reckoning with the U.S. Role in Global Ocean Plastic Waste calls for a national strategy by the end of 2022 to reduce the nation's contribution to global ocean plastic waste at every step - from production to its entry into the environment - including by substantially reducing U.S. solid waste generation. This report also recommends a nationally-coordinated and expanded monitoring system to track plastic pollution in order to understand the scales and sources of U.S. plastic waste, set reduction and management priorities, and measure progress.
Keywords: Environment and Environmental Studies

Wildland Fires: Toward Improved Understanding and Forecasting of Air Quality Impacts: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Wildland fires pose a growing threat to air quality and human health. Fire is a natural part of many landscapes, but the extent of area burned and the severity of fires have been increasing, concurrent with human movement into previously uninhabited fire-prone areas and forest management practices that have increased fuel loads. These changes heighten the risk of exposure to fire itself and emissions (smoke), which can travel thousands of miles and affect millions of people, creating local, regional, and national air quality and health concerns. To address this growing threat, the National Academies brought together atmospheric chemistry and health research communities, natural resource managers, and decision makers to discuss current knowledge and needs surrounding how wildland fire emissions affect air quality and human health. Participants also explored opportunities to better bridge these communities to advance science and improve the production and exchange of information. This publication summarizes the workshop discussions and themes that emerged throughout the meeting.
Keywords: Earth Sciences

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine (The National Academies Press, 2015)
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a "return to normal." But for many American communities, pre-disaster conditions are far from optimal. Large segments of the U.S. population suffer from preventable health problems, experience inequitable access to services, and rely on overburdened health systems. A return to pre-event conditions in such cases may be short-sighted given the high costs - both economic and social - of poor health. Instead, it is important to understand that the disaster recovery process offers a series of unique and valuable opportunities to improve on the status quo. Capitalizing on these opportunities can advance the long-term health, resilience, and sustainability of communities - thereby better preparing them for future challenges. Healthy, Resilient, and Sustainable Communities After Disasters identifies and recommends recovery practices and novel programs most likely to impact overall community public health and contribute to resiliency for future incidents. This book makes the case that disaster recovery should be guided by a healthy community vision, where health considerations are integrated into all aspects of recovery planning before and after a disaster, and funding streams are leveraged in a coordinated manner and applied to health improvement priorities in order to meet human recovery needs and create healthy built and natural environments. The conceptual framework presented in Healthy, Resilient, and Sustainable Communities After Disasters lays the groundwork to achieve this goal and provides operational guidance for multiple sectors involved in community planning and disaster recovery. Healthy, Resilient, and Sustainable Communities After Disasters calls for actions at multiple levels to facilitate recovery strategies that optimize community health. With a shared healthy community vision, strategic planning that prioritizes health, and coordinated implementation, disaster recovery can result in a communities that are healthier, more livable places for current and future generations to grow and thrive - communities that are better prepared for future adversities.
Keywords: Health and Medicine; Conflict and Security Issues

Advancing the Science of Climate Change - National Research Council (The National Academies Press, 2010)
Climate change is occurring, is caused largely by human activities, and poses significant risks for—and in many cases is already affecting—a broad range of human and natural systems. The compelling case for these conclusions is provided in Advancing the Science of Climate Change, part of a congressionally requested suite of studies known as America's Climate Choices. While noting that there is always more to learn and that the scientific process is never closed, the book shows that hypotheses about climate change are supported by multiple lines of evidence and have stood firm in the face of serious debate and careful evaluation of alternative explanations. As decision makers respond to these risks, the nation's scientific enterprise can contribute through research that improves understanding of the causes and consequences of climate change and also is useful to decision makers at the local, regional, national, and international levels. The book identifies decisions being made in 12 sectors, ranging from agriculture to transportation, to identify decisions being made in response to climate change. Advancing the Science of Climate Change calls for a single federal entity or program to coordinate a national, multidisciplinary research effort aimed at improving both understanding and responses to climate change. Seven cross-cutting research themes are identified to support this scientific enterprise. In addition, leaders of federal climate research should redouble efforts to deploy a comprehensive climate observing system, improve climate models and other analytical tools, invest in human capital, and improve linkages between research and decisions by forming partnerships with action-oriented programs.
Keywords: Environment and Environmental Studies; Earth Sciences

Motivating Local Climate Adaptation and Strengthening Resilience: Making Local Data Trusted, Useful, and Used - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Local communities are already experiencing dire effects caused by climate change that are expected to increase in frequency, intensity, duration, and type. Public concern about climate-related challenges is increasing, available information and resources on climate risks are expanding, and cities across the country and the globe are developing approaches to and experience with measures for mitigating climate impacts. Building and sustaining local capacities for climate resilience requires both resilient physical and social infrastructure systems and inclusive, resilient communities. At the request of the Federal Emergency Management Agency, Motivating Local Climate Adaptation and Strengthening Resilience provides guidance for active and ongoing efforts to move science and data into action and to enable and empower applied research that will strengthen capacities for hazard mitigation and resilience in communities, across the nation, and around the world.
Keywords: Environment and Environmental Studies

Advancing Health and Resilience in the Gulf of Mexico Region: A Roadmap for Progress - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Consequences of natural disasters and the COVID-19 pandemic have taken a cumulative toll on the health and well-being of people in the Gulf of Mexico region. Long-standing societal challenges related to racism, poverty, education, housing, and underemployment are compounding the trauma, leading to chronic stress for many Gulf residents. The Committee on Progress Toward Human Health and Community Resilience in the Gulf of Mexico Region new report, Advancing Health and Community Resilience in the Gulf of Mexico Region: A Roadmap for Progress, explores key challenges and priorities in Gulf states, including Alabama, Florida, Louisiana, Mississippi, and Texas and evaluates recent progress. The report also makes recommendations for closing critical gaps and implementing transformative approaches that focus on the diverse needs and experiences of people who live and work in the Gulf region.
Keywords: Health and Medicine; Environment and Environmental Studies